Risk and Responsibility: Evaluating the Efficacy of Framed Health Communication Strategies During a Pandemic - Wahyudi, Jaemi (Indonesian Scientific Publication, 2024)
This study investigates the effectiveness of gain- versus loss-framed messaging in shaping public intentions to vaccinate during health crises such as the COVID-19 pandemic. Drawing on prospect theory and behavioral communication principles, the research examines how framing influences vaccine uptake and explores demographic and cultural moderators of framing impact. Using a randomized survey experiment, the study found that loss-framed messages increased vaccination intention by 27% compared to gain-framed messages (Cohen’s d = 0.76). The effect was particularly strong among older adults and individuals with high trust in health authorities. Practically, these results suggest that public health campaigns should prioritize loss-framed content in high-risk populations while pairing it with clear guidance on action steps. The findings highlight the ethical need to balance persuasive urgency with empathy and inclusivity. Theoretically, this study advances the application of prospect theory in health communication, while practically, it informs targeted strategies for reducing vaccine hesitancy through culturally attuned and multi channel outreach.